Zróżnicowanie przestrzenne temperatury powietrza w sezonie letnim na zachodnim wybrzeżu Spitsbergenu - Marciniak, Kazimierz; Przybylak, Rajmund (1987)
The report is based on the air temperature measurements in 17 points localized on the west coast of Spitsbergen (Tab. 1 and Fig. 1) for the period July – August 1979 and 1980. The analysis of areal differentiation was made by using the mean daily values of 10-days and month’s periods (tab. 1) and extremal and absolute temperatures (tab. 2). The results of long-term measurements of the air temperature in permanent meteorological station were used too. In the summer season the warmest are arear non-glaciated situated at the head of Isfjorden (Svalbard Lufthavn). The mean differences reach in July 1.5°C (in particular year even up to 2°C), and in August 0.8°C, as compared with the coast of open sea (Isfjord Radio). The north-west and middle-west coasts of Spitsbergen are warmer for 1°C in average than the south-west coast which is approached by the cold South-Cape Current and often exposed to the cyclons moving from the Iceland low. Great areal differentiation occurs in the belt of few kilometers along the coast as a result of the topography and kind of subsoil (ice-covered or free of ice). The differences between thermal conditions of particular coastal parts of Spitsbergen reveal especially in sunny days and change relative to the direction of air advection (circulation).